STUDI TINGKAT PENDAPATAN PETANI SEBELUM DAN SESUDAH KONVERSI LAHAN PERTANIAN KE PERKEBUNAN KELAPA SAWIT DI DESA PAKAWA KECAMATAN PASANGKAYU KABUPATEN MAMUJU UTARA - Armin, Armin (Katalogis, 2017)
The purpose of this study to determine changes in the income level of farmers before and after the conversion of agricultural land into oil palm plantations in the village Pakawa. The research area village of Bamba Apu, Lala, Kumu and Mandar Dua (Salu Apu). With the selection of the sample proportional random sampling as many as 68 families, consisting of 22 families Bunggu Tribe, 22 families Bugis tribe and 24 families Mandar tribe. The results showed that the income level of farmers from the three tribes (Bunggu, Bugis and Mandar) greater after land conversion than before land conversion, socio-economic characteristics of the three tribal farmers are classified in socio-economic conditions are adequate.